Peran Dinas Kearsipan dan Perpustakaan Kabupaten Badung Dalam Pelestarian Naskah Kuno Lontar - Diastari, Ni Putu Febry; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 3 No 2 (2023), 2023)
This study aims to examine the role of the Badung Regency Archives and Libraries Office in the preservation of ancient lontar manuscripts. This institution has an important responsibility in safeguarding and maintaining this priceless cultural heritage. This study uses a descriptive research method with a qualitative approach. Data collection techniques used are observation to the library, conducting interviews, documentation and literature study. This study analyzes the policies, programs and practices carried out by these institutions. The results of this study indicate that the Badung Regency Archives and Libraries Service has a significant role in the preservation of ancient lontar manuscripts.